Why Malformations of Cortical Development Cause Epilepsy - Represa, Alfonso (Frontiers in Neuroscience, 2019)
Malformations of cortical development (MCDs), a complex family of rare disorders, result from alterations of one or combined developmental steps, including progenitors proliferation, neuronal migration and differentiation. They are important cause of childhood epilepsy and frequently associate cognitive deficits and behavioral alterations. Though the physiopathological mechanisms of epilepsy in MCD patients remain poorly elucidated, research during the past decade highlighted the contribution of some factors that will be reviewed in this paper and that include: i) the genes that caused the malformation, that can be responsible for a significant reduction of inhibitory cells (e.g. ARX gene) or be inducing cell-autonomous epileptogenic changes in affected neurons (e.g. mutations on the mTOR pathway); ii) the alteration of cortical networks development induced by the malformation that will also involve adjacent or distal cortical areas apparently sane so that the epileptogenic focus might be more extended that the malformation or even localized at distance from it; iii) the normal developmental processes that would influence and determine the onset of epilepsy in MCD patients, particularly precocious in most of the cases.